Method for improving cracking tendency of aluminum bronze material through microalloying
Through microalloying treatment and addition of specific elements, combined with vacuum induction smelting, hot extrusion, cold drawing and stress removal annealing processes, the problem of Cu-Al series alloy cracking after use is solved, significantly improving the strength and toughness of the material , achieves the effect of reducing the tendency of cracking while ensuring strength.
Patent Information
- Application Number
- CN202411179922.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2024-12-27
AI Technical Summary
Existing Cu-Al series alloys are prone to cracking failure accidents after use. How to prevent cracking while ensuring the strength of the material is a problem to be solved.
Through microalloying, Fe, Ni, Mn, RE elements are added, and the deformation amount and annealing temperature are controlled in process steps such as vacuum induction smelting, hot extrusion, cold drawing and stress removal annealing to form a small second phase Particles enhance the matrix structure and reduce the tendency to crack, while adding toughened materials such as titanium dioxide, yttrium oxide, zirconia and calcium silicate powder to improve the toughness and corrosion resistance of the material.
The strength, hardness and corrosion resistance of aluminum bronze materials are significantly improved, plasticity and toughness are improved, cracking tendencies are reduced, and the comprehensive properties of the material are improved, including tensile strength and yield strength are improved by optimizing the microstructure.
Smart Images

Figure CN119194135A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aluminum bronze materials, and in particular to a method for improving the cracking tendency of aluminum bronze materials through microalloying. Background Art
[0002] Cu-Al alloys are a type of copper-based alloy widely used in the industrial field. They usually improve their mechanical properties through solid solution strengthening and aging treatment. The principle of solid solution strengthening is that when aluminum bronze is heated to a high temperature and kept warm for a period of time, the alloy elements will dissolve into the copper matrix. At this time, it is cooled rapidly. The alloy elements cannot precipitate to form a solid solution, which causes the copper lattice lattice distortion and forms a stress field. When the alloy is deformed, the elastic stress field around the dislocation interacts with the stress field formed by the alloy elements, increasing the friction resistance of the dislocation movement, thereby producing a solid solution strengthening effect. In addition, the electrostatic interaction between the charged solute atoms dissolved in the copper matrix and the dislocations hinders the movement of the dislocations; in addition, the movement of the dislocations changes the distribution of the alloy elements in the solid solution in a short-range ordered or segregated form, increasing the overall energy of the system and increasing the deformation resistance required for slip.
[0003] Dispersion strengthening is an important metal strengthening mechanism in materials science. The state of the supersaturated solid solution formed after solid solution is unstable. When the alloy is aged, the aluminum bronze solid solution and secondary aging new heat treatment process experimental research material dissolved into the matrix will undergo desolvation and form second-phase particles. The dislocation will continue to move around the second-phase particles and leave a dislocation ring around the particles, thereby strengthening the material.
[0004] However, the existing common Cu-Al series alloy products are prone to failure accidents such as cracking during later use. How to prevent the surface of aluminum bronze materials from cracking while ensuring the strength of aluminum bronze materials remains a problem to be solved. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a method for improving the cracking tendency of aluminum bronze material by microalloying.
[0006] The technical solution of the present invention is: a method for improving the cracking tendency of aluminum bronze material by microalloying, comprising the following steps: S1, vacuum induction melting
[0007] According to mass percentage, 27-42% of Cu-Al intermediate alloy, 0.1-0.18% of Fe block, 0-0.2% of Ni block, 0.1-0.18% of Mn block, 0-0.2% of RE and the balance of electrolytic Cu plate are crushed, ground and mixed uniformly to obtain raw material powder; vacuum induction melting is performed on the raw material powder at a temperature of 1100-1400° C. for 50-70 minutes to obtain a copper-aluminum composite alloy billet;
[0008] S2. Hot extrusion treatment
[0009] The copper-aluminum composite alloy billet is hot extruded at a temperature of 850-950°C with a maximum extrusion pressure of 2400-2600T, and is naturally cooled after extrusion to obtain a copper-aluminum composite alloy profile;
[0010] S3, cold drawing treatment
[0011] The copper-aluminum composite alloy profile is subjected to cold drawing at room temperature, wherein the deformation amount of the cold drawing is 15-25%;
[0012] S4, stress relief annealing
[0013] The cold-drawn copper-aluminum composite alloy profile is subjected to stress relief annealing, the annealing temperature is 380-420°C, and the annealing time is 2-4h.
[0014] Description: By adding Fe, Ni, Mn, RE and other elements to make aluminum bronze microalloy, the strength, hardness and corrosion resistance of aluminum bronze can be significantly improved; the addition of these elements can form fine second phase particles, strengthen the matrix, improve the plasticity and toughness of the material, and reduce the tendency to crack; by controlling the deformation amount to 15-25%, the strength of the material can be improved without destroying the structure of the material, while maintaining a certain plasticity; appropriate cold deformation can induce work hardening, further improving the tensile strength and yield strength of the material; by controlling the annealing temperature and time at 380-420℃, 2-4h, the internal stress generated during the processing can be effectively eliminated, the material can be prevented from deformation, the size can be stabilized, and a certain plasticity can be restored to reduce the tendency to crack;
[0015] The dispersion strengthening mechanism not only improves the strength of the material, but also maintains good plasticity and toughness. This is because the fine second phase particles will not significantly increase the brittleness while improving the strength of the material, which enables the material to maintain a certain deformation ability when subjected to high stress.
[0016] Furthermore, the Al content in the Cu-Al intermediate alloy described in S1 accounts for 20-30% of the total mass of the Cu-Al intermediate alloy.
[0017] Description: The right proportion of Al can improve the processing properties of copper alloys, help reduce the risk of cracks and fractures during the manufacturing process, and improve the yield rate; the addition of Al can adjust the thermal expansion coefficient of the alloy to make it closer to the requirements of certain specific applications, which is very beneficial in environments with large temperature changes.
[0018] Furthermore, the raw material powder in S1 further includes a toughening material accounting for 1 to 3% of the total mass of the raw material powder;
[0019] The preparation method of the toughening material is as follows: titanium dioxide, yttrium oxide, zirconium oxide and calcium silicate powder are ball-milled and mixed in a mass ratio of 4:1-3:0.8-1:2-3 to obtain metal mixed powder; the metal mixed powder is introduced into a resistance furnace under an argon environment for primary calcination, and the calcined powder is obtained after cooling with the furnace; the calcined powder is mixed with dehydrated charcoal particles in a mass ratio of 1:1-1.5, and then anhydrous ethanol accounting for 20-30% of the mass ratio of the calcined powder is added, and wet-milling is performed uniformly using a ball mill; then the mixture is placed in a drying box and dried at 80-100°C to obtain an oxide material; the oxide material is re-calcined, and after cooling, the oxide material is placed in dilute hydrochloric acid with a mass concentration of 5-15% to soak and remove impurities, washed with deionized water, and dried at 60-80°C; the dried oxide material is surface treated to obtain a toughening material.
[0020] Description: Using titanium dioxide, yttrium oxide, zirconium oxide and calcium silicate powder as toughening material raw materials can effectively improve the fracture toughness of the alloy, reduce the expansion of cracks, and improve the impact resistance of the material; these materials form fine particles or fibrous reinforcement phases in the alloy, which can prevent further expansion of cracks and improve the overall toughness of the alloy; the addition of titanium dioxide can enhance the stability and wear resistance of the alloy and improve its corrosion resistance. Yttrium oxide and zirconium oxide have good high-temperature stability and can improve the strength and oxidation resistance of the alloy at high temperatures, which is especially important for components that need to work in high-temperature environments; the addition of toughening materials helps to refine the grains of the alloy and optimize the microstructure of the alloy, thereby improving The comprehensive properties of high alloys include strength, plasticity and wear resistance; the addition of yttria, zirconium oxide and calcium silicate can form a dense oxide film, improve the corrosion resistance and oxidation resistance of the alloy surface, and extend the service life of the alloy; fine toughening material particles can improve the machinability and formability of the alloy, reduce wear and crack generation during processing, and improve production efficiency; initial calcination helps to optimize the microstructure of the material, such as refining the grains, reducing defects, and providing easier-to-handle powder for subsequent processing steps such as wet grinding and re-calcination; re-calcination helps to further optimize the microstructure of the material, reduce defects, and improve the hardness, toughness and other properties of the material, which is particularly important for enhancing the material's resistance to crack growth.
[0021] Furthermore, the particle size of the yttrium oxide powder is 60-100 nm, the particle size of the zirconium oxide powder is 20-80 nm, and the particle size of the calcium silicate powder is 1-10 μm.
[0022] Description: Nano-level yttrium oxide and zirconium oxide powders have a larger specific surface area, which helps to disperse more evenly in the alloy matrix, reduce agglomeration, and improve the micro-uniformity of the material; the combination of nano-level powder and micron-level calcium silicate powder can form a good interface effect, enhance the bonding force between different components, improve the overall strength and toughness of the composite material, promote the optimization of the microstructure of the material, refine the grains, and form a denser structure, thereby improving the hardness, strength and wear resistance of the material; the addition of nano-level powder can improve the fluidity of the alloy, reduce cracks and defects during processing, and improve the machinability of the material.
[0023] Furthermore, the rotation speed of the ball milling mixing is 70-90 r / min, the ball-to-material ratio is 4-6:1, and the ball milling time is 4-6 hours.
[0024] Description: By ball milling the material, its specific surface area can be increased, the reaction activity of the material can be improved, which is beneficial to the subsequent chemical reaction or physical processing process; controlling the ball milling process parameters can make the material efficiently refined and evenly mixed, significantly shorten the reaction time in the processing process, and improve production efficiency.
[0025] Furthermore, the initial calcination temperature is 1100-1300° C., and the initial calcination time is 70-90 min; the re-calcination temperature is 1100-1150° C., and the calcination time is 50-70 min.
[0026] Description: At the initial calcination high temperature of 1100-1300℃, raw materials such as yttrium oxide, zirconium oxide and calcium silicate can fully react to form the required solid solution or composite phase, thereby improving the chemical stability and thermal stability of the material; for zirconium oxide, this temperature range helps to transform from the monoclinic phase to the more stable tetragonal or cubic phase, thereby enhancing the toughness of the material; at high temperatures, any residual moisture or volatile impurities will be completely eliminated to ensure the purity of the material; controlling the calcination time and temperature helps to refine the grains, optimize the microstructure of the material, reduce defects, and improve the strength and toughness of the material.
[0027] The re-calcination process is carried out at a slightly lower temperature, which can further consolidate and optimize the crystal phase formed in the initial calcination and improve the thermal and chemical stability of the material. Compared with the initial calcination, a lower temperature and a shorter time can effectively control the growth of grains and prevent excessive grain growth from causing material performance degradation. Re-calcination helps to further optimize the microstructure of the material, such as reducing porosity and increasing the density of the material, thereby improving the mechanical properties of the material. The surface of the material after re-calcination is cleaner, which is conducive to subsequent surface treatment and improves the bonding strength with the alloy matrix powder.
[0028] Furthermore, the surface treatment method is: soak the dried oxide material in a treatment liquid for reaction for 30 to 50 minutes, and the reaction temperature is 50 to 60°C; then take it out, wash it with deionized water and dry it, and finally put it into a resistance furnace for secondary calcination, and cool it with the furnace. The calcination time is 2 to 3 hours, and the calcination temperature is 1100 to 1150°C.
[0029] Description: By reacting in a specific treatment liquid, impurities on the surface of the oxide material can be removed to generate a highly active surface structure. For composite materials or coating materials, surface treatment can enhance the interfacial bonding between the matrix and the coating or reinforcement phase, thereby improving the overall performance of the material, such as strength and toughness; high-temperature secondary calcination can improve the thermal stability of the material, so that it can still maintain good performance in a high temperature environment; the surface-treated material has more uniform properties, which can reduce cracks and deformation in subsequent processing.
[0030] Furthermore, the treatment liquid comprises: a mixed aqueous solution of 8-14 g / L copper sulfate, 9-11 g / L sodium citrate, 7-13 g / L sodium ethylenediaminetetraacetate, 5-15 mL / L acetone, 0.4-0.8 mg / L dithiocarbamate, 10-15 mg / L ferrous chloride, 8-10 mg / L 1,10-phenanthroline, 0.5-2 mL / L propylene glycol and 0.1-2 mL / L glycerol; the purity of the acetone is 99.5-99.9%.
[0031] Description: Copper sulfate and ferrous chloride, as oxidants, can remove the oxide layer on the metal surface, promote the activation of the metal surface, and improve its reactivity with other components; 1,10-phenanthroline, as a chelating agent, helps to further clean and stabilize the metal surface; sodium citrate and sodium ethylenediaminetetraacetate, as chelating agents, can control the deposition rate of metal ions, avoid unevenness caused by too fast deposition, and ensure the uniformity and quality of the deposited layer; acetone can reduce the interference of impurities and ensure the purity of the deposition process. Acetone also has good solubility and volatility, which helps to control the thickness and properties of the deposited layer; dithiocarbamates can enhance the adhesion of the deposited layer to the substrate and improve the stability and wear resistance of the deposited layer; propylene glycol and glycerol, as additives, can improve the density and uniformity of the deposited layer, reduce the porosity, and improve the density and anti-corrosion performance of the deposited layer.
[0032] Furthermore, before the copper-aluminum composite alloy profile in S3 is cold deformed, a mixed liquid accounting for 5 to 10% of the mass of the copper-aluminum composite alloy profile is evenly applied on its surface, and the mixed liquid is composed of poly-α-olefin and zinc disulfide mixed in a mass ratio of 2 to 5:1.
[0033] Description: Add the extreme pressure additive zinc disulfide to the polyalphaolefin oil in proportion to improve lubricity and reduce friction and heat generated during the drawing process, which helps prevent material cracking and ensures the smooth progress of the drawing process, while also improving the surface quality and mechanical properties of the finished product.
[0034] The beneficial effects of the present invention are:
[0035] The invention can significantly improve the strength, hardness and corrosion resistance of aluminum bronze materials by adding Fe, Ni, Mn and RE elements through microalloying, add toughening materials to form fine second phase particles, strengthen the matrix, improve the plasticity and toughness of the material and reduce the cracking tendency; in the vacuum induction melting process, the high temperature condition is conducive to the uniform distribution of elements and forms a more uniform alloy structure; hot extrusion treatment can further optimize the microstructure of the material, and refine the grains of the material and improve its mechanical properties by controlling the extrusion temperature and pressure; cold drawing treatment is carried out at room temperature, and by controlling the deformation amount, the strength of the material can be improved without destroying the material structure, while maintaining a certain plasticity; appropriate cold deformation amount can induce work hardening, and further improve the tensile strength and yield strength of the material; stress relief annealing is a heat treatment process carried out after cold drawing, and by controlling the annealing temperature and time, the internal stress generated in the processing process can be effectively eliminated, the material deformation can be prevented, the size can be stabilized, and a certain plasticity can be restored to reduce the cracking tendency. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The metallographic structure diagram is 50 times that of the sample in Example 1 of the present invention;
[0037] Figure 2 It is a 50-fold metallographic structure diagram of the sample of Example 3 of the present invention;
[0038] Figure 3 It is a 50-fold metallographic structure diagram of the sample of Example 12 of the present invention;
[0039] Figure 4 It is a metallographic structure diagram 50 times that of the sample of comparative example 1 of the present invention;
[0040] Figure 5 It is a 50-fold metallographic structure diagram of the sample of comparative example 2 of the present invention;
[0041] Figure 6 It is a 50-fold metallographic structure diagram of the sample of comparative example 3 of the present invention;
[0042] Figure 7 It is a metallographic structure diagram 50 times that of the sample of comparative example 4 of the present invention;
[0043] Figure 8 is an outer surface diagram of the sample of Example 1 of the present invention before the simulated welding experiment;
[0044] Fig. 9 is an outer surface diagram of the sample after the simulated welding experiment of Example 1 of the present invention;
[0045] Fig.10 This is the outer surface diagram of the sample of comparative example 5 of the present invention before the simulated welding experiment;
[0046] Fig.11 This is the outer surface diagram of the sample of comparative example 5 of the present invention after the simulated welding experiment;
[0047] Fig.12 It is a left view of the outer surface of the sample of control example 5 of the present invention after the simulated welding experiment. DETAILED DESCRIPTION
[0048] In order to further illustrate the method and effect of the present invention, the technical solution of the present invention will be clearly and completely described in combination with experiments.
[0049] Embodiment 1:
[0050] A method for improving the cracking tendency of aluminum bronze materials by microalloying, comprising the following steps:
[0051] S1. Vacuum induction melting
[0052] In percentage by mass, 13.5% of Cu-Al intermediate alloy, 0.14% of Fe block, 0.1% of Ni block, 0.14% of Mn block, 0.1% of RE and the rest of electrolytic Cu plate are crushed, ground and mixed evenly to obtain raw material powder; vacuum induction melting is performed on the raw material powder at a temperature of 1250° C. for 60 min to obtain a copper-aluminum composite alloy billet; the Al content in the Cu-Al intermediate alloy accounts for 25% of the total mass of the Cu-Al intermediate alloy;
[0053] The raw material powder also includes a toughening material accounting for 2% of the total mass of the raw material powder;
[0054] The preparation method of the toughening material is as follows: titanium dioxide, yttrium oxide, zirconium oxide and calcium silicate powder are ball-milled and mixed in a mass ratio of 4:2:0.9:2.5 to obtain a metal mixed powder; the metal mixed powder is introduced into a resistance furnace under an argon environment for initial calcination, and the calcined powder is obtained after cooling with the furnace; the calcined powder is mixed with dehydrated charcoal particles in a mass ratio of 1:1.25, and then anhydrous ethanol accounting for 25% of the mass ratio of the calcined powder is added, and wet-milled uniformly using a ball mill; then the mixture is placed in a drying box and dried at 90°C to obtain an oxide material; the oxide material is re-calcined, and after cooling, it is placed in dilute hydrochloric acid with a mass concentration of 10% to soak and remove impurities, washed with deionized water, and dried at 70°C; the dried oxide material is surface treated to obtain a toughening material;
[0055] The particle size of the yttrium oxide powder is 75-85 nm, the particle size of the zirconium oxide powder is 45-55 nm, and the particle size of the calcium silicate powder is 4-6 μm;
[0056] The ball milling speed is 80r / min, the ball-to-material ratio is 5:1, and the ball milling time is 5h;
[0057] The initial calcination temperature is 1200°C and the initial calcination time is 80 minutes; the re-calcination temperature is 1125°C and the calcination time is 60 minutes;
[0058] The surface treatment method is as follows: immerse the dried oxide material in a treatment solution for reaction for 40 minutes at a reaction temperature of 55°C; then remove it, wash it with deionized water and dry it, and finally put it into a resistance furnace for secondary calcination and cool it with the furnace. The calcination time is 2.5 hours and the calcination temperature is 1125°C.
[0059] The treatment liquid is composed of: a mixed aqueous solution of 11 g / L copper sulfate, 10 g / L sodium citrate, 10 g / L sodium ethylenediaminetetraacetate, 10 mL / L acetone, 0.6 mg / L dithiocarbamate, 12.5 mg / L ferrous chloride, 9 mg / L 1,10-phenanthroline, 1.25 mL / L propylene glycol and 1 mL / L glycerol; the purity of the acetone is 99.7%;
[0060] S2. Hot extrusion treatment
[0061] The copper-aluminum composite alloy billet is hot extruded at a temperature of 900°C with a maximum extrusion pressure of 2500T, and is naturally cooled after extrusion to obtain a copper-aluminum composite alloy profile;
[0062] S3, cold drawing treatment
[0063] The copper-aluminum composite alloy profile is subjected to cold drawing at room temperature, wherein the deformation amount of the cold drawing is 20%; before the copper-aluminum composite alloy profile is subjected to cold deformation, a mixed liquid accounting for 7.5% of the mass of the copper-aluminum composite alloy profile is evenly applied on the surface of the copper-aluminum composite alloy profile, wherein the mixed liquid is a mixture of poly-α-olefin and zinc disulfide in a mass ratio of 3.5:1;
[0064] S4, stress relief annealing
[0065] The copper-aluminum composite alloy profile after cold drawing is subjected to stress relief annealing, the annealing temperature is 400°C, and the annealing time is 3h.
[0066] Example 2: This example is basically the same as Example 1, except that, by mass percentage, 27% of the Cu-Al intermediate alloy, 0.1% of the Fe block, 0.1% of the Mn block and the remainder of the electrolytic Cu plate are crushed, ground and mixed evenly to obtain raw material powder; the raw material powder is vacuum induction melted at a temperature of 1100°C for 50 minutes to obtain a copper-aluminum composite alloy billet.
[0067] Example 3: This example is basically the same as Example 1, except that 42% of Cu-Al intermediate alloy, 0.18% of Fe block, 0.2% of Ni block, 0.18% of Mn block, 0.2% of RE and the remainder of electrolytic Cu plate are crushed, ground and mixed evenly to obtain raw material powder; the raw material powder is vacuum induction melted at a temperature of 1400°C for 70 minutes to obtain a copper-aluminum composite alloy billet.
[0068] Example 4: This example is basically the same as Example 1, except that the copper-aluminum composite alloy billet is hot extruded at a temperature of 850°C, the maximum extrusion pressure is 2400T, and it is naturally cooled after extrusion to obtain a copper-aluminum composite alloy profile.
[0069] Example 5: This example is basically the same as Example 1, except that the copper-aluminum composite alloy billet is hot extruded at a temperature of 950°C with a maximum extrusion pressure of 2600T, and is naturally cooled after extrusion to obtain a copper-aluminum composite alloy profile.
[0070] Example 6: This example is basically the same as Example 1, except that the copper-aluminum composite alloy profile is cold deformed at room temperature, and the deformation amount is 15%.
[0071] Example 7: This example is basically the same as Example 1, except that the copper-aluminum composite alloy profile is cold deformed at room temperature, and the deformation amount is 25%.
[0072] Example 8: This example is basically the same as Example 1, except that the copper-aluminum composite alloy profile after cold drawing is subjected to stress relief annealing, the annealing temperature is 380° C., and the annealing time is 2 h.
[0073] Example 9: This example is basically the same as Example 1, except that the copper-aluminum composite alloy profile after cold drawing is subjected to stress relief annealing, the annealing temperature is 420° C., and the annealing time is 4 hours.
[0074] Example 10: This example is basically the same as Example 1, except that the raw material powder in S1 further includes a toughening material accounting for 1% of the total mass of the raw material powder.
[0075] Example 11: This example is basically the same as Example 1, except that the raw material powder in S1 further includes a toughening material accounting for 3% of the total mass of the raw material powder.
[0076] Example 12: This example is basically the same as Example 1, except that the preparation method of the toughening material is as follows: titanium dioxide, yttrium oxide, zirconium oxide and calcium silicate powders are ball-milled and mixed in a mass ratio of 4:1:0.8:2 to obtain a metal mixed powder; the metal mixed powder is introduced into a resistance furnace under an argon environment for initial calcination, and the calcined powder is obtained after cooling in the furnace; the calcined powder is mixed with dehydrated charcoal particles in a mass ratio of 1:1, and then anhydrous ethanol accounting for 20% of the mass ratio of the calcined powder is added, and wet-milled evenly using a ball mill; then placed in a drying oven and dried at 80°C to obtain an oxide material; the oxide material is re-calcined, and after cooling, it is placed in a dilute hydrochloric acid with a mass concentration of 5% to soak and remove impurities, washed with deionized water, and dried at 60°C; the dried oxide material is surface treated to obtain a toughening material; the ball milling rotation speed is 70r / min, the ball-to-material ratio is 4:1, and the ball milling time is 4h.
[0077] Example 13: This example is basically the same as Example 1, except that the preparation method of the toughening material is as follows: titanium dioxide, yttrium oxide, zirconium oxide and calcium silicate powders are ball-milled and mixed in a mass ratio of 4:3:1:3 to obtain a metal mixed powder; the metal mixed powder is introduced into a resistance furnace under an argon environment for initial calcination, and the calcined powder is obtained after cooling in the furnace; the calcined powder is mixed with dehydrated charcoal particles in a mass ratio of 1:1.5, and then anhydrous ethanol accounting for 30% of the mass ratio of the calcined powder is added, and wet-milled evenly using a ball mill; then placed in a drying oven and dried at 100°C to obtain an oxide material; the oxide material is re-calcined, and after cooling, it is placed in a dilute hydrochloric acid with a mass concentration of 15% to soak and remove impurities, washed with deionized water, and dried at 80°C; the dried oxide material is surface treated to obtain a toughening material; the ball milling rotation speed is 90r / min, the ball-to-material ratio is 6:1, and the ball milling time is 6h.
[0078] Example 14: This example is basically the same as Example 1, except that the particle size of the yttrium oxide powder is 60-65 nm, the particle size of the zirconium oxide powder is 20-25 nm, and the particle size of the calcium silicate powder is 1-2 μm.
[0079] Example 15: This example is basically the same as Example 1, except that the particle size of the yttrium oxide powder is 95-100 nm, the particle size of the zirconium oxide powder is 75-80 nm, and the particle size of the calcium silicate powder is 9-10 μm.
[0080] Example 16: This example is basically the same as Example 1, except that the initial calcination temperature is 1100°C and the initial calcination time is 70 min; the re-calcination temperature is 1100°C and the calcination time is 50 min.
[0081] Example 17: This example is basically the same as Example 1, except that the initial calcination temperature is 1300°C, and the initial calcination time is 90 minutes; the calcination temperature of the re-calcination is 1150°C, and the calcination time is 70 minutes.
[0082] Example 18: This example is basically the same as Example 1, except that the surface treatment method is: soak the dried oxide material in the treatment liquid for reaction for 30 minutes, and the reaction temperature is 50°C; then take it out, wash it with deionized water and dry it, and finally put it into a resistance furnace for secondary calcination and cool it with the furnace. The calcination time is 2 hours and the calcination temperature is 1100°C.
[0083] Example 19: This example is basically the same as Example 1, except that the surface treatment method is: soak the dried oxide material in the treatment liquid for reaction for 50 minutes, and the reaction temperature is 60°C; then take it out, wash it with deionized water and dry it, and finally put it into a resistance furnace for secondary calcination and cool it with the furnace. The calcination time is 3 hours and the calcination temperature is 1150°C.
[0084] Example 20: This example is basically the same as Example 1, except that the treatment liquid comprises: a mixed aqueous solution of 8 g / L copper sulfate, 9 g / L sodium citrate, 7 g / L sodium ethylenediaminetetraacetate, 5 mL / L acetone, 0.4 mg / L dithiocarbamate, 10 mg / L ferrous chloride, 8 mg / L 1,10-phenanthroline, 0.5 mL / L propylene glycol and 0.1 mL / L glycerol; the purity of the acetone is 99.5%.
[0085] Example 21: This example is basically the same as Example 1, except that the treatment liquid comprises: a mixed aqueous solution of 14 g / L copper sulfate, 11 g / L sodium citrate, 13 g / L sodium ethylenediaminetetraacetate, 15 mL / L acetone, 0.8 mg / L dithiocarbamate, 15 mg / L ferrous chloride, 10 mg / L 1,10-phenanthroline, 2 mL / L propylene glycol and 2 mL / L glycerol; the purity of the acetone is 99.9%.
[0086] Example 22: This example is basically the same as Example 1, except that, before the copper-aluminum composite alloy profile described in S3 is cold deformed, a mixed liquid accounting for 5% of the mass of the copper-aluminum composite alloy profile is evenly applied on its surface, and the mixed liquid is composed of poly-α-olefin and zinc disulfide mixed in a mass ratio of 2:1.
[0087] Example 23: This example is basically the same as Example 1, except that, before the copper-aluminum composite alloy profile in S3 is cold deformed, a mixed liquid accounting for 10% of the mass of the copper-aluminum composite alloy profile is evenly applied on its surface, and the mixed liquid is composed of poly-α-olefin and zinc disulfide mixed in a mass ratio of 5:1.
[0088] Comparative Example 1: Example 1 was used as a reference, but no toughening material was added.
[0089] Comparative Example 2: Taking Example 1 as a reference, conventional water seal cooling was adopted after S2 extrusion was completed.
[0090] Comparative Example 3: With reference to Example 1, the mixed liquid is not applied on the surface of the copper-aluminum composite alloy profile in S3 before cold deformation.
[0091] Comparative Example 4: With reference to Example 1, the raw material powder in S1 is 42% Cu-Al intermediate alloy and the rest of the electrolytic Cu plate which is crushed, ground and then mixed evenly.
[0092] Comparative Example 5: With reference to Example 1, the raw material powder in S1 is 42% Cu-Al intermediate alloy and the remainder of electrolytic Cu plate which is crushed, ground and mixed evenly, and no toughening material is added to the raw material powder.
[0093] In order to explore the performance of aluminum bronze materials treated in Examples 1, 3, 12 and Comparative Examples 1 to 4, the main materials were determined according to the experimental formula and 7 groups of samples were obtained for ammonia fumigation test. The specific exploration is as follows:
[0094] 1. Explore the influence of vacuum induction melting process parameters on the properties of aluminum bronze materials:
[0095] like Figure 1 , 2 As shown, by comparing Examples 1 and 3, it can be seen that the vacuum induction melting process parameters have no obvious effect on the performance of the aluminum bronze material, the surface flatness of Example 1 is better, and the aluminum bronze materials prepared by using the process parameter values of Examples 1 and 3 have good performance in preventing cracking tendency.
[0096] 2. Investigate the effect of adding toughening materials on the properties of aluminum bronze materials:
[0097] like Figure 1 , 3 As shown, by comparing Examples 1 and 12, it can be seen that the change in the process parameters for preparing the toughened material has no significant effect on the properties of the aluminum bronze material, and both have good performance in preventing cracking tendency.
[0098] like Figure 1 , 4 As shown, by comparing Example 1 and Control Example 1, it can be seen that the aluminum bronze material with added toughening material has better performance in preventing cracking tendency, the aluminum bronze material prepared by the process of Control Example 1 has very slight cracking phenomenon, and the aluminum bronze material prepared by the process of the embodiment has better performance in preventing cracking tendency.
[0099] 3. Explore the effect of the change of cooling method in S2 on the properties of aluminum bronze material:
[0100] like Figure 1 , 5 As shown, by comparing Example 1 and Control Example 2, it can be seen that the aluminum bronze material prepared according to the method of Example 1 has better performance in preventing cracking tendency, and the structure of Control Example 2 has obvious cracking. The change of cooling method can have a certain effect on the performance of aluminum bronze material.
[0101] 4. Explore the effect of surface coating treatment on the performance of aluminum bronze materials before cold deformation of copper-aluminum composite alloy profiles:
[0102] like Figure 1 , 6 As shown, by comparing Example 1 with Control Example 3, it can be seen that: the surface coating treatment has a certain influence on the performance of the aluminum bronze material, but the effect is not obvious, and the samples that are not coated and cold deformed have a slight tendency to crack.
[0103] 5. Explore the influence of raw material powder formula on the performance of aluminum bronze materials:
[0104] like Figure 1 , 7 As shown, compared with Example 1 and Control Example 4, the difference in the performance of preventing cracking tendency is quite obvious. The surface of the sample produced by the method of Control Example 4 has obvious cracking structure. It can be seen that the change of the raw material powder formula can have a great influence on the performance of aluminum bronze material. The aluminum bronze material sample produced by the method of Example 1 has the best performance of preventing cracking tendency.
[0105] A simulated welding experiment was conducted on Example 1 and Comparative Example 5, and the experimental conditions were: keeping the temperature at 700° C. for 2 h;
[0106] like Figure 8 , 9 As shown, the aluminum bronze material sample produced by the process method of Example 1 did not crack. Fig.10 , 11 As shown in Figures 1 and 12, the aluminum bronze material sample produced by the process method of Control Example 5 showed obvious cracking. It can be seen that the change of the raw material formula can have a great impact on the performance of the aluminum bronze material. The aluminum bronze material sample produced by the method of Example 1 has the best performance in preventing cracking tendency.
Claims
1. A method for improving the cracking tendency of aluminum bronze materials by microalloying, characterized in that: The following steps are involved: S1. Vacuum induction melting According to mass percentage, 27-42% of Cu-Al intermediate alloy, 0.1-0.18% of Fe block, 0-0.2% of Ni block, 0.1-0.18% of Mn block, 0-0.2% of RE and the balance of electrolytic Cu plate are crushed, ground and mixed uniformly to obtain raw material powder; vacuum induction melting is performed on the raw material powder at a temperature of 1100-1400° C. for 50-70 minutes to obtain a copper-aluminum composite alloy billet; S2. Hot extrusion treatment The copper-aluminum composite alloy billet is hot extruded at a temperature of 850-950°C with a maximum extrusion pressure of 2400-2600T, and is naturally cooled after extrusion to obtain a copper-aluminum composite alloy profile; S3, cold drawing treatment The copper-aluminum composite alloy profile is subjected to cold drawing at room temperature, wherein the deformation amount of the cold drawing is 15-25%; S4, stress relief annealing The cold-drawn copper-aluminum composite alloy profile is subjected to stress relief annealing, the annealing temperature is 380-420°C, and the annealing time is 2-4h.
2. The method for improving the cracking tendency of aluminum bronze material by microalloying according to claim 1, characterized in that: S1 The Al content in the Cu-Al intermediate alloy accounts for 20-30% of the total mass of the Cu-Al intermediate alloy.
3. The method for improving the cracking tendency of aluminum bronze material by microalloying according to claim 1, characterized in that: S1 The raw material powder also includes a toughening material accounting for 1 to 3% of the total mass of the raw material powder; The preparation method of the toughening material is as follows: titanium dioxide, yttrium oxide, zirconium oxide and calcium silicate powder are ball-milled and mixed in a mass ratio of 4:1-3:0.8-1:2-3 to obtain metal mixed powder; the metal mixed powder is introduced into a resistance furnace under an argon environment for primary calcination, and the calcined powder is obtained after cooling with the furnace; the calcined powder is mixed with dehydrated charcoal particles in a mass ratio of 1:1-1.5, and then anhydrous ethanol accounting for 20-30% of the mass ratio of the calcined powder is added, and wet-milling is performed uniformly using a ball mill; then the mixture is placed in a drying box and dried at 80-100°C to obtain an oxide material; the oxide material is re-calcined, and after cooling, the oxide material is placed in dilute hydrochloric acid with a mass concentration of 5-15% to soak and remove impurities, washed with deionized water, and dried at 60-80°C; the dried oxide material is surface treated to obtain a toughening material.
4. The method for improving the cracking tendency of aluminum bronze material by microalloying according to claim 1, characterized in that: The particle size of the yttrium oxide powder is 60-100 nm, the particle size of the zirconium oxide powder is 20-80 nm, and the particle size of the calcium silicate powder is 1-10 μm.
5. The method for improving the cracking tendency of aluminum bronze material by microalloying according to claim 1, characterized in that: The rotation speed of the ball milling mixing is 70-90 r / min, the ball-to-material ratio is 4-6:1, and the ball milling time is 4-6 hours.
6. The method for improving the cracking tendency of aluminum bronze material by microalloying according to claim 1, characterized in that: The initial calcination temperature is 1100-1300° C., and the initial calcination time is 70-90 minutes; the re-calcination temperature is 1100-1150° C., and the calcination time is 50-70 minutes.
7. The method for improving the cracking tendency of aluminum bronze material by microalloying according to claim 1, characterized in that: The surface treatment method is as follows: immerse the dried oxide material in a treatment solution for reaction for 30 to 50 minutes at a reaction temperature of 50 to 60°C; then remove the material, wash it with deionized water and dry it, and finally place it in a resistance furnace for secondary calcination and cool it with the furnace. The calcination time is 2 to 3 hours and the calcination temperature is 1100 to 1150°C.
8. The method for improving the cracking tendency of aluminum bronze material by microalloying according to claim 1, characterized in that: The treatment liquid comprises: a mixed aqueous solution of 8-14 g / L copper sulfate, 9-11 g / L sodium citrate, 7-13 g / L sodium ethylenediaminetetraacetate, 5-15 mL / L acetone, 0.4-0.8 mg / L dithiocarbamate, 10-15 mg / L ferrous chloride, 8-10 mg / L 1,10-phenanthroline, 0.5-2 mL / L propylene glycol and 0.1-2 mL / L glycerol; the purity of the acetone is 99.5-99.9%.
9. The method for improving the cracking tendency of aluminum bronze material by microalloying according to claim 1, characterized in that: S3 Before the copper-aluminum composite alloy profile is cold deformed, a mixed liquid accounting for 5 to 10% of the mass of the copper-aluminum composite alloy profile is evenly applied on its surface, wherein the mixed liquid is a mixture of polyalphaolefin and zinc disulfide in a mass ratio of 2 to 5:1.
